Borderline virginities: sacred and secular virgins in late antiquity - Undheim, Sissel (Taylor and Francis, 2017)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Preface -- Abbreviations -- 1 Introduction. Sancta virginitate: limits and border zones -- Defining virginity -- The Roman virgo -- Virgo, virginitas and variations of chastity -- Sacred virgins -- Comparative virginiology: the echo of the Church Fathers -- Fixity, flexity, and fluidity -- Borderline virginities -- 2 Roman virginities. Between rhetorics, ideals, and "reality" -- Virginity at the cultural turn -- The Social Value of Virginity -- Felices nuptae: virgin and bride -- The social status of virgins -- The social status of Vestal virgins -- Christian virgins and the Roman aristocracy -- Slave virgins? -- Libertae -- Redefining noble virginity? -- The Virgin Effect -- Roman virgins and religious rituals -- Virginal protection 1 -- Virginal protection 2 -- Sacrificial imagery -- Chosen by the gods? -- A family affair? The problem of free will -- Age of Virgins -- The age of virgins at consecration -- Those who belong to the kingdom of heaven -- Epigraphic evidence and the age of virgins -- The age of Vestals at captio: virgins and children -- A due date for virginity? -- Agency, age and the consecration of virgins -- Virginal Insignia -- The official dress of the Vestal virgins -- "The garments of Christ" -- De habitu virginum - or "how to recognize a virgin" 1 -- Virginal appearance -- The young and noble virgins of Rome -- 3 Ungendering virginity? Virginal paradoxes and paradoxical virginities -- Becoming male? Gender-bending "female" virgins -- Male Virgins and Genderless Virginity -- Male virgins in non-Christian sources? -- Like angels on earth -- Eunuchs and male virginity -- Male Virgins and Genderless Virginity -- Virginity and clerical celibacy -- Virgin Fathers of the Church? -- Male virgins in funerary inscriptions -- Just like a virgin?